The interaction energy of two uniformly charged spheroids. Example of deformed nuclei - S. Ya. Goroshchenko; A. V. Nesterov; V. A. Nesterov (Ядерна фізика та енергетика)
We consider the question of calculations of the interaction energy of two uniformly charged spheroids. Three cases are realized in the software: the interaction of a uniformly charged spheroid with a point charge; interaction of two coaxial spheroids; and the general case of mutual position of spheroids. The presented programs are initially oriented for nuclear calculations. However, by a change of numerical coefficients, they can be used in the calculations of the interaction energy in any cases of spheroidal objects with the uniformly distributed charge or mass.